2023
DOI: 10.1186/s40798-022-00533-9
|View full text |Cite
|
Sign up to set email alerts
|

Is There Evidence for the Development of Sex-Specific Guidelines for Ultramarathon Coaches and Athletes? A Systematic Review

Abstract: Background There is evidence of sex differences in the physiology of endurance exercise, yet most of the advice and guidelines on training, racing, nutrition, and recovery for ultramarathons are based on research that has largely excluded female athletes. The objective was therefore to review the current knowledge of sex differences in ultramarathon runners and determine if sufficient evidence exists for providing separate guidelines for males and females. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…These authors suggested that, from a performance perspective, the higher running economy may partially compensate for the lower V O 2max in female runners [ 87 ]. However, controversial findings exist on sex differences in fatigue resistance and pacing in road and trail ultra-marathons [ 81 , 88 , 89 ]. Some authors reported greater fatigue resistance and better pacing in female ultra-marathon participants [ 81 , 89 ], whereas others found that women tended to slow down more than men in the later stages of trail running ultra-marathons, despite the terrain (uphill and downhill) [ 88 ].…”
Section: Uphill/downhill Locomotionmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors suggested that, from a performance perspective, the higher running economy may partially compensate for the lower V O 2max in female runners [ 87 ]. However, controversial findings exist on sex differences in fatigue resistance and pacing in road and trail ultra-marathons [ 81 , 88 , 89 ]. Some authors reported greater fatigue resistance and better pacing in female ultra-marathon participants [ 81 , 89 ], whereas others found that women tended to slow down more than men in the later stages of trail running ultra-marathons, despite the terrain (uphill and downhill) [ 88 ].…”
Section: Uphill/downhill Locomotionmentioning
confidence: 99%
“…However, controversial findings exist on sex differences in fatigue resistance and pacing in road and trail ultra-marathons [ 81 , 88 , 89 ]. Some authors reported greater fatigue resistance and better pacing in female ultra-marathon participants [ 81 , 89 ], whereas others found that women tended to slow down more than men in the later stages of trail running ultra-marathons, despite the terrain (uphill and downhill) [ 88 ]. Further studies are needed to better understand sex differences in the energetics and biomechanics of incline walking and running, and fatigue resistance and pacing strategies in ultra-marathons controlling for fitness levels, anthropometric differences, menstrual cycle effect and the level of relative effort used for testing both sexes.…”
Section: Uphill/downhill Locomotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent upgrades in co-operative drafting strategies during racing ( 54 ) likely benefit women more than men over road racing distances given that they can be paced for the entirety of the race as opposed to only an initial portion, although this does not explain why women are also improving at faster rates on the track. Another consideration is that modern developments in training design and nutritional supplementation strategies which more precisely target female physiology may have also contributed to the latest breakthroughs in performances ( 55 , 56 ).…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the work done by Kelly [ 1 ], who conducted a systematic review (SR) that aimed to review the current knowledge of sex differences in ultramarathon runners and determine if sufficient evidence exists for providing separate guidelines for males and females. First, we want to compliment the author on the relevance of this investigation.…”
mentioning
confidence: 99%